Лексико-фразеологічні засоби відображення стереотипних уявлень про обмежені ментальні здібності людини - Рогач, Оксана Олексіївна; Rohach, O. О. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано особливості номінації обмежених ментальних здібностей людини лексико-фра¬зеологічними засобами англійської мови, установлено стереотипні уявлення англійської спільноти про розу¬мову діяльність людей, окреслено диференційні ознаки осіб з обмеженими ментальними здібностями, а також проведено компонентний аналіз семантичної структури базових одиниць лексико-семантичного поля «обме¬жені розумові здібності» з урахуванням семантичної структури лексеми fool та її дериватів. The article deals with the analysis of the nomination of mental abilities of mentally handicapped people by means of lexical and phraseological units of the English language, with the investigation of the stereotyped images of the mentally handicapped people that were formed in the English speaking community, with the definition of the distinctive features of the people that obtain such characteristics, with the componential analysis of the semantic structure of the basic units of the lexical semantic field “limited mental abilities”. A special attention has been paid to the differentiation and analysis of the lexical and phraseological units that represent the main distinctive features of the people who are mentally handicapped. The main ones are incurability, dangers, universality, foolish acts, talkativeness, recklessness, gullibility, and wisdom. It has been pointed out that there is a direct correlation between mental abilities of a person and his financial and material wealth, career and social status that are reflected in the lexical phraseological systems of the English language.
Lexical and Phraseological Means of Expressing Stereotyped Images of Mentally Handicapped People
Keywords: обмежені ментальні здібності; limited mental abilities; вторинна номінація; secondary nomination; стереотип; stereotype